Regulating Li electrodeposition by constructing Cu–Sn nanotube thin layer for reliable and robust anode‐free all‐solid‐state batteries - Jaeik Kim; Seungwoo Lee; Jeongheon Kim; Joonhyeok Park; Hyungjun Lee; Jiseok Kwon; Seho Sun; Junghyun Choi; Ungyu Paik; Taeseup Song (Carbon Energy)
Abstract Anode‐free all‐solid‐state batteries (AF‐ASSBs) have received significant attention as a next‐generation battery system due to their high energy density and safety. However, this system still faces challenges, such as poor Coulombic efficiency and short‐circuiting caused by Li dendrite growth. In this study, the AF‐ASSBs are demonstrated with reliable and robust electrochemical properties by employing Cu–Sn nanotube (NT) thin layer (~1 µm) on the Cu current collector for regulating Li electrodeposition. LixSn phases with high Li‐ion diffusivity in the lithiated Cu–Sn NT layer enable facile Li diffusion along with its one‐dimensional hollow geometry. The unique structure, in which Li electrodeposition takes place between the Cu–Sn NT layer and the current collector by the Coble creep mechanism, improves cell durability by preventing solid electrolyte (SE) decomposition and Li dendrite growth. Furthermore, the large surface area of the Cu–Sn NT layer ensures close contact with the SE layer, leading to a reduced lithiation overpotential compared to that of a flat Cu–Sn layer. The Cu–Sn NT layer also maintains its structural integrity owing to its high mechanical properties and porous nature, which could further alleviate the mechanical stress. The LiNi0.8Co0.1Mn0.1O2 (NCM)|SE|Cu–Sn NT@Cu cell with a practical capacity of 2.9 mAh cm−2 exhibits 83.8% cycle retention after 150 cycles and an average Coulombic efficiency of 99.85% at room temperature. It also demonstrates a critical current density 4.5 times higher compared to the NCM|SE|Cu cell.